Role Women Formal Education On Enhanced Family Welfare (Case studies : Cililin Village District Cililin Bandung West District) - ANDINI PRIHATI (NIM 25407040), ISMA
In general, the poor people of low education level of the high number of women and illiteracy are preferred due to education for men who are expected to become head of the family. While the poor in the role of women as the economic backbone of the family is very significant. They were able to contribute economically to both family and society so that income is an important factor in determining the quality of life and direct impact on family welfare. Education as investment considered as a form of human capital which in turn can improve the welfare of his life in the future. Therefore, it should along with the high level of formal education and women's contribution in improving the welfare of his family are expected to increase investment so that the government has been issued for the provision of education infrastructure is also to be useful. This study aims to understand the role of formal education level of women in the village Cililin to increase the welfare of the family. The study is expected to give a picture how the relationship is the case, what factors preference involvement of educated women in formal employment and the factors that affect the contribution of women workers have a formal requirement of the family. This is in order to improve the quality of human resources so that women able to eradicate poverty in the Village area Cililin in the future. To be able to understand the relationship of formal education level of women with increased family welfare, then conducted a qualitative descriptive analysis. The first stage is to identify the relationship between the level of formal education with the welfare indicator used is the large income, financing the basic needs (school fees of children, daily consumption expenditure and improving the condition of the home facility) and the purchase of family assets. Next analyzed the relationship is not there with the family on the welfare of women have a basic, medium and high. The next stage is the search for the factors that hinder and encourage educated women to work and formal factors that cause differences in the amount of the contribution that women can be given to their families. The findings of this study show that formal education can be useful in order to improve the welfare of his family at the time the woman is able to climb higher education. In general secondary education and below does not provide the expertise and capabilities that can be used as stock for their own work at home. In general, also, it does not formally educated women to work and work that is due to internal conditions, family conditions and external conditions. In addition to the causes of the diversity of women workers have contributed to the formal needs of the family there is a level of formal education, greater income, the contribution of the basic needs of families and contributing to the purchase of family assets. Inputs for the government in the region in order to reduce the poverty through increased welfare of the family that is connected with improving the quality of women's rural areas is done through the improvement of formal education in rural areas and the development of training for women, a formal mechanism that supported capital and good marketing.